2017
DOI: 10.1159/000484566
|View full text |Cite
|
Sign up to set email alerts
|

Sugar-Sweetened Beverages and Weight Gain in Children and Adults: A Systematic Review from 2013 to 2015 and a Comparison with Previous Studies

Abstract: Objective: Partly inconsistent findings from previous reviews have fueled discussions on the impact of sugar-sweetened beverages (SSBs) on obesity development. The aim was to systematically review the recent evidence in children and adults. Methods: Data were retrieved from the databases MEDLINE, EMBASE, and Cochrane library for the period January 2013 to October 2015. A systematic review of prospective cohort studies and randomized controlled trials (RCTs) relating SSBs to weight measures was conducted. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
180
3
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(213 citation statements)
references
References 51 publications
(87 reference statements)
8
180
3
4
Order By: Relevance
“…However, in particular, increased availability of highly processed fast food (Zobel et al, 2016) and increased consumption of high-energy soft drinks are suggested to have importantly contributed to the obesity epidemic (Basu et al, 2013). There are convincing epidemiological data showing that soft drink consumption is associated with higher BMI (Garduño-Alanís et al, 2019) and increased weight gain in both children and adults (Luger et al, 2017;Malik et al, 2013). Physiologically, the association between soft-drink consumption and increased energy intake is expected, since high-energy drinks have only a weak satiety response (Maersk et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, in particular, increased availability of highly processed fast food (Zobel et al, 2016) and increased consumption of high-energy soft drinks are suggested to have importantly contributed to the obesity epidemic (Basu et al, 2013). There are convincing epidemiological data showing that soft drink consumption is associated with higher BMI (Garduño-Alanís et al, 2019) and increased weight gain in both children and adults (Luger et al, 2017;Malik et al, 2013). Physiologically, the association between soft-drink consumption and increased energy intake is expected, since high-energy drinks have only a weak satiety response (Maersk et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…an important, modifiable risk factor for childhood obesity. 1−7 Several high-profile randomized controlled trials, 1,2 as well as systematic reviews and meta-analyses 3,8 have consistently identified cross-sectional and longitudinal associations between SSBs and various indices of obesity. In longitudinal studies, the magnitude of weight change over short-term follow-up is typically small (on the order of 0.06 kg/m 2 per year per additional SSB), 3 potentially necessitating either long-term follow-up or large sample sizes for detection.…”
Section: T a G G E D P Sugar-sweetened Beverage (Ssb) Consumption Ismentioning
confidence: 99%
“…Unhealthy food choices are a known risk factor that contribute to the increasing prevalence of non-communicable diseases and premature deaths [44,45]. In particular the consumption of sugarsweetened beverages in this context have been highlighted [30,35]. Consequently, dietary intake has become a recognized public health priority [10], and support for healthier food selection behavior is of key importance to achieve changes in consumer behavior and population health [23].…”
Section: Motivationmentioning
confidence: 99%